SOCIAL AND SPIRITUAL FACTORS OF PATRIOTISM IN MILITARY SERVANTS - Tursunmurad Doniyorovich Mamatqabilov (Web of Journals Publishing, 2023)
The article reflects the importance of realizing peace and stability in the country as the highest good through social, spiritual and educational support for military personnel and, in connection with this, the importance of living and working with a sense of belonging for every citizen living in the country.
Keywords: activities of military personnel, spiritual and educational work, social and cultural life, patriotism.